Integrasi Pendidikan Lingkungan dalam Upaya Pelestarian Kawasan Perlindungan Alam di Kota Salatiga - Adi Saputro, Purnomo; Aida, Elsa Nur (Universitas Negeri Semarang, 2025)
This study analyzes the role of spatial education in improving public understanding of land use control in Salatiga City based on the implementation of the Regional Spatial Plan (RTRW). Land use mismatch of 20% of the total area of ​​nature protection areas is mainly due to land conversion into residential and commercial areas. This study uses quantitative methods with overlay analysis, quantitative SWOT, and time series 2018–2023. Data were collected through questionnaires to 100 employees of related agencies. The results of the study indicate that low public awareness and weak law enforcement are the main obstacles in the implementation of the Regional Spatial Plan (RTRW). However, there is good integration between spatial education and increasing public compliance with land use regulations from areas with higher levels of socialization of the Regional Spatial Plan (RTRW) have lower levels of land mismatch. Therefore, integration of spatial education is needed through collaboration between the government, educational institutions, and local communities to improve the effectiveness of land use control and maintain the sustainability of nature protection areas in Salatiga City.